2004
DOI: 10.1063/1.1778472
|View full text |Cite
|
Sign up to set email alerts
|

Bright white light electroluminescent devices based on a dye-dispersed polyfluorene derivative

Abstract: A series of efficient and bright white light-emitting diodes were fabricated using the blends of two fluorene-derived fluorescent dyes, (4,7-bis-(9,9,9′,9′-tetrahexyl-9H,9′H-[2,2′]bifluoren-7-yl)-benzo[1,2,5]thiadiazole) (FFBFF-emits green) and (4,7-bis-[5-(9,9-dihexyl-9H-fluoren-2-yl)-thiophen-2-yl]-benzo[1,2,5]thiadiazole) (FTBTF-emits red) in an efficient blue-emitting polyfluorene-derived copolymer (poly[(9,9-bis(4-di(4-n-butylphenyl)aminophenyl))]-stat-(9,9-bis(4-(5-(4-tert-butylphenyl)-2-oxadiazolyl)-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…4 Kim et al showed that bright white PLEDs could be produced using a blend of two fluorescent dyes in a blue emission polyfluorene derivative as a light-emitting layer. 8 Mikami et al reported that white PLEDs with high brightness, efficiency, and color purity could be fabricated using a single light emitting layer of fluorescent dye doped polymers. 10 Gong et al showed that white PLEDs with excellent electroluminescence (EL) properties could be fabricated using a phosphorescent-Ir complex doped polymer as a lightemitting layer.…”
Section: Introductionmentioning
confidence: 99%
“…4 Kim et al showed that bright white PLEDs could be produced using a blend of two fluorescent dyes in a blue emission polyfluorene derivative as a light-emitting layer. 8 Mikami et al reported that white PLEDs with high brightness, efficiency, and color purity could be fabricated using a single light emitting layer of fluorescent dye doped polymers. 10 Gong et al showed that white PLEDs with excellent electroluminescence (EL) properties could be fabricated using a phosphorescent-Ir complex doped polymer as a lightemitting layer.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies toward realizing PWLEDS have been reported, such as the multilayer-device system [3][4][5] and the single-layer polymer-blend system. [6][7][8][9][10][11][12] Nevertheless, both of them have some disadvantages, for instance, the interfacial mixing of different layers for the former and the intrinsic phase separation for the latter, which limit their applications. These problems are avoidable in a single-polymer system.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] One of main approaches to producing WPLEDs is to use a polymer blend system, such as three-polymer blends containing red, green and blue polymers, 13 and blends consisting of two or three kinds of fluorescent dyes in an efficient blue-emitting polymer matrix. 14,15 However, it is difficult to obtain highly efficient and color stable WPLEDs using polymer blend systems due to undesirable Forster-type energy transfer between chromophores. Another approach is to use single layer devices made from homopolymers 16,17 or copolymers.…”
Section: Introductionmentioning
confidence: 99%